PERGESERAN BUSANA ONE SET DARI PIYAMA MENJADI BUSANA SEHARI_HARI - Ummah, Nisa Haritsatul; Falah, Asep Miftahul (Jurusan Seni Rupa ISBI Bandung, 2022)
Trends in the fashion world are constantly changing and these changes are influenced by many factors, one of which is the social and economic conditions at that time. The Covid-19 pandemic requires everyone to adapt to the new normal (era new normal), including trends in the fashion world. The fashion trend in question is the shift in one set of clothing from pajamas to everyday clothing. In essence, most of the fashion in the past came from the upper class and flowed to the lower classes. Ordinary people always hope to improve their social position by following the fashion of those who have rights. But at this time the trend was started by celebrities not the nobility. As in the one-set fashion which is currently on the rise, starting with celebrities who use these clothes for outdoor occasions, then various groups of people start to follow them to use these clothes also on outdoor occasions. Keywords: One set clothing, pajamas, outdoor clothing, fashion trends, nightwear——————————————————————————-Tren pada dunia fashion terus berubah dan perubahan tersebut dipengaruhi oleh banyak faktor, salah satunya adalah keadaan sosial dan ekonomi pada saat itu. Pandemi Covid-19 mengharuskan setiap orang untuk beradaptasi dengan tatanan normal baru (era new normal), termasuk tren dalam dunia fesyen. Tren fesyen yang dimaksud yaitu pergeseran busana one set dari piayama menjadi busana sehari-hari. Pada hakekatnya, sebagian besar fashion di masa lalu berasal dari kelas atas dan mengalir ke kelas-kelas di bawahnya. Orang biasa selalu berharap meningkatkan posisi sosial mereka dengan mengikuti fashion orang-orang yang memiliki hak. Namun di masa ini tren dimulai oleh para selebriti bukan kaum bangsawan. Seperti pada busana one set yang sekarang sedang naik daun, berawal dari selebriti yang menggunakan busana tersebut untuk digunakan pada kesempatan outdoor, lalu mulai diikuti oleh berbagai macam kalangan untuk menggunakan busana ini juga pada kesempatan outdoor.Kata Kunci: Busana one set, piyama, busana outdoor, tren fesyen, baju tidur